1993
DOI: 10.1520/jfs13457j
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Forensic Specimens for the Polymerase Chain Reaction (PCR) Analysis

Abstract: Purification methods of deoxyribonucleic acid (DNA) from degraded and contaminated forensic samples were investigated for polymerase chain reaction (PCR) analysis. DNA extracted from putrefied tissue or bloodstains sometimes contained the copurified contaminant, that was identified as the porphyrin compound (hematin). When contaminated but less degraded DNA was analyzed by PCR, it was necessary to eliminate the impurity by anion exchange column chromatography or chelating resin preparation, and ultrafiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Higher concentrations were obtained from the liver, kidney and brain tissues, similar to those obtained by Atmadja et al (1995) for human tissues. The OD260/OD280 ratio values satisfied those suggested by Sambrook et al (1989), ≥ 1.8, which were higher than those obtained by Akane et al (1993) and Atmadja et al (1995).…”
Section: Resultssupporting
confidence: 61%
“…Higher concentrations were obtained from the liver, kidney and brain tissues, similar to those obtained by Atmadja et al (1995) for human tissues. The OD260/OD280 ratio values satisfied those suggested by Sambrook et al (1989), ≥ 1.8, which were higher than those obtained by Akane et al (1993) and Atmadja et al (1995).…”
Section: Resultssupporting
confidence: 61%
“…To assess the sensitivity of the IPC to inhibition, a series of artificially inhibited DNA extracts were examined using the triplex qPCR assay. Twenty identical tubes of non-degraded DNA were treated with different amounts of hematin, a known PCR inhibitor [24], such that the final concentrations of hematin in the standard 20 mL qPCR assays ranged from 0 to 160 mM. Each sample was assayed in duplicate with the nuTH01-nuCSF-IPC triplex qPCR assay, and the results are summarized in Table 4.…”
Section: Detection Of Pcr Inhibition With the Nuth01-nucsf-ipc Triplementioning
confidence: 99%
“…Features making qPCR particularly attractive for forensic applications are: (i) qPCR assays can be designed to quantify specific genomes of interest; (ii) the assays can be sensitive enough to detect only a few copies or even a single copy of target DNA; (iii) qPCR dynamic detection ranges readily span the roughly three orders of magnitude (e.g., 30 pg to 30 ng of nuclear DNA) needed for most forensic applications; and (iv) the experimental protocols for real-time qPCR quantitations are straightforward, labor-saving, and amenable to automation. Moreover, the use of target-specific detection www.elsevier.com/locate/forsciint Forensic Science International 158 (2006) [14][15][16][17][18][19][20][21][22][23][24][25][26] chemistries (e.g., TaqMan 1 [3] or Molecular Beacon [4] probes) makes it possible to design multiplex, real-time qPCR assays that can simultaneously quantify more than one target in a sample, offering the possibility for saving time, labor, and extracted DNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the success rate of diagnostic PCR analysis is lowered by the presence of PCRinhibitory substances [2], a problem especially prominent in forensic DNA analysis due to the often complex sampling environment at crime scenes [3][4][5]. Recently, we reported that 12% of volume crime saliva stains with adequate DNA amounts analyzed at our laboratory still produced negative DNA profiles due to the presence of inhibitors [6].…”
Section: Introductionmentioning
confidence: 99%